Colostrum traits and newborn body weight and growth: comparison between single and twin underfed sheep pregnancies - Turín, Jesús; Sales, Francisco; Peralta, Oscar A.; De los Reyes, Mónica; Borie, Consuelo; Carrasco, Albert; González-Bulnes, Antonio; Parraguez, Víctor H. (Frontiers in Veterinary Science, 2023)
Maternal nutrition during gestation plays an important role in colostrum production, postnatal growth, and survival of newborn lambs, especially in twin gestations. This research aimed to investigate the effects of chronic natural undernutrition on colostrum traits and early lamb´s postnatal growth born from single and twin sheep pregnancies developed in a restrictive prairie, representative of southern Patagonia. Single- and twin-bearing ewes (n=20 per group) were maintained grazing in a natural pasture. At 140 days of gestation, ewes were placed in individual pens for lambing control. Colostrum was collected immediately after delivery and at 12, 24 and 36 h postpartum, for determination of yield and composition. Maternal blood was obtained at 140 days of gestation and at lambing for plasma glucose, progesterone, 17β-estradiol and IgG determination. Newborn lamb blood for determining glycaemia and IgG was collected at birth and at 12, 24, 36 and 120 h after birth. Lamb mortality and growth was assessed from birth until 30 days of life. No differences were observed in progesterone and 17β-estradiol. There were no differences in colostrum yields and fat components, however single- had higher values of protein and lactose than twin-bearing ewes (P < 0.05 for both). Singletons had higher glycaemia than twins at 12 h postpartum (102.2±32.8 vs 73.4±29.9 mg/dL, P < 0.05). Colostrum IgG content was similar at delivery but higher in single ewes at 12 and 24 h, reaching a similar values at 36 h (4.7±9.7 and 5.8±7.7 mg/mL in single and twin pregnancies, respectively). Newborn IgG was higher in singletons compared to twins at least until 48 h of life. Lams body weight was always superior in singleton than twins from birth until 30 days of life. Mortality did not differ during the first week of life, but it increased significantly only in twins until day 30 of life. Undernourishment in pregnant ewes affected colostrum quantity and quality, resulting in a lower postnatal growth and a higher mortality in twins. Alternative managements favoring fetal growth, birth weight and neonatal viability in twin sheep pregnancies are needed, when flocks are breed under harsh environments.